# `cos(x+y)*cos(x-y)=cos^2x-sin^2y` ``

hala718 | Certified Educator

calendarEducator since 2008

starTop subjects are Math, Science, and Social Sciences

`cos(x+y)*cos(x-y)= cos^2 x - sin^2 x`

`` We will use trigonometric identities to prove the identities.

We know that:

`cosa*cosb= (1/2)(cos(a-b)+cos(a+b)) `

`==gt cos(x+y)*cos(x-y)= (1/2)(cos(x+y-x+y)+cos(x+y+x-y)) `

`==gt cos(x+y)*cos(x-y)= (1/2)(cos(2y) + cos(2x)) `

`==gt cos(x+y)*cos(x-y)= (1/2)((1-2sin^2 y)+(2cos^2x -1)) `

`==gt cos(x+y)*cos(x-y)= (1/2)( 2cos^2 x - 2sin^2y +1 -1) `

`==gt cos(x+y)*cos(x-y)= (1/2)2(cos^2 x-sin^2y) `

`==gt cos(x+y)*cos(x-y)= cos^2 x - sin^2 y.`

``

check Approved by eNotes Editorial

jacqueshaw | Student

first cos(a+b)=cosacosb-sinasinb and cos(a-b)=cosacosb+sinasinb

therefore, cos(x+y).cos(x-y)=(cosxcosy-sinxsiny)(cosxcosy+sinxsiny)

=cos^2 xcos^2 y - sinxsinycosxcosy + sinxsinycosxcosy - sin^2 xsin^2 y

=cos^2 xcos^2 y-sin^2 xsin^2 y

sin^2 y+cos^2 y = 1

= cos^2 x (1-sin^2 y)-sin^2 y (1-cos^2 x)

= cos^2 x - sin^2 y cos^2 x - sin^2 y +sin^2 y cos^2 x

= cos^2 x - sin^2 y